Azygos Lobe: The Prevalence, Dimensions, and Estimated Volume of Thirteen Cases Investigated by Computed Tomography - Mehrdad Ghorbanlou; Fatemeh Moradi (Anatomical Sciences Journal, 2021)
Introduction: Surgery and diagnostic radiology have emphasized the significance of the azygos lobe as a normal variant of lungs. Therefore, this study investigated the prevalence, dimensions, and estimated volume of thirteen azygos lobes. Methods: The chest CT scans of 789 patients (490 men and 297 women) were retrospectively analyzed for one year (2020-2021), in an Iranian population. Then, the dimensions of the azygos lobe, including Maximum Width (MW), Maximum Length (ML), and Maximum Height (MH), and also Estimated Volume (EV) were reported in total, men, and women. Results: The total prevalence of the azygos lobe was 1.65%; it was 1.83%, and 1.34% in men and women, respectively, showing a higher prevalence in men. Also, Mean±SD MW, ML, MH, and EV were 47.76±19.28 mm, 60.03±15.91 mm, 46.44±11.91mm,, and 88.831±80.18ml, respectively. No significant difference was detected between mean MW, ML, and MH. Although the dimensions and estimated volume were higher in men than in women, the differences were insignificant. Conclusion: The literature provides no reliable and sufficient data about the size of azygos lobes, especially among the Iranian population. Data reported in this study can be of importance in diagnosis and preventing surgical complications, regarding the presence of the azygos lobe.